Language Function on Gender Representation in the English Textbooks of Indonesian Junior High Schools: Shaping Students' Social Awareness and Identity - Sebastianus Menggo; Glaudia Ningsi Putri Harten; Tobias Gunas; Sabina Ndiung; Antonio Constantino Soares (Yayasan Keluarga Guru Mandiri, 2026)
The linguistic functions used in textbooks strengthen students' understanding of how gender representation is expressed. This study aims to examine the power of gender-based language functions in an English book. This manuscript incorporates a qualitative descriptive approach. Data were collected through content analysis in examining gender representation and the variety of language functions. Data were analyzed in three stages: identification, categorization, and interpretation, aimed at determining the patterns of gender representation and the use of language functions in textbooks. The results showed that males were represented at a higher rate (54.13%) than females (45.87%) based on criteria for measuring gender representation, including pictorial illustrations, characters, gender mentions, role models, activities, and patterns of referencing females and males. A number of the six types of language functions used by the authors in their books, namely Referential, Emotive, Conative, Phatic, Metalingual, and Poetic, represent the highest female gender compared to the other five types. These findings conclude that language functions play a substantial role in shaping gender representation, promoting established beliefs about the roles of men and women. This study broadens applied linguistics in education by showing how textbook constructs of language proficiency shape students' perspectives on social consciousness and gender identity.